(3JGQjN GdESdGe hWHbGJ GdeTGgjQ hGdCYdGes - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s ((3MSf Hf Ydi Hf eMeO GdRQcTi GdMfai s)
(3ChdgG (B:s
(3bGd GdTgjQ GdEeGe TeS GdOjf CeG HYO , agPG cJGH fGaY hfYhP HGddg ef Yde dGjfaY LeYJg hHbjJ Ydjg hGSJNQLJg ef YOI JUGfja ef Chd JGQjN GdESdGe Edi YUQfG gPG ef hajGJ GdcHGQ s
(3BNQgG (B:s
(3aQLYJ abGdJ (B: (3Cbdfi , bGd (B: (3CbdJc hbO NWH Udi Gddg Ydjg hSde Ce gGfF HfJ CHj WGdH hUajI hde jbV dg Cf jJRhL Hgf , SHMGfg hJYGdi CYde EfJgJ GdJQLeI hHJeGegG Je GdLRA GdChd hGdMeO ddg s
(3HgG WeS ai ChQGbgG GdCNjQI NGUIs
(3HgG fXGe GdJYbjHis
(3ai GdeYgO fSN CNQi HQbe (B98 (3, (B569(3, (B949 (3, (B1447 (3, (B1448 (3JGQjNs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs